Morphological Differentiation among Estuarine Catfishes of the Family Ariidae of the Matang Mangrove Ecosystem, Perak, Malaysia - H.R, Singh,; V.C, Chong,; Ismail M, Zakaria- (Malaysian Journal of Science, 2003)
Morphometric and meristic analysis indicates that the six species of the ariid catfishes of the genera $Arius$ recorded from Sungai Selinsing of the Matang mangroves can be distinguished on the basis of their pre-dorsal length, inter-orbital width, number of gill rakers and head length. $Arius$ $sangor$ has the longest pre-dorsal length and the widest inter-orbital width while $Arius$ $truncatus$ has the lowest number of gill rakers. $Arius$ $maculatus$ is separated from all other ariids of the area in having the highest number of gill rakers while $A.$ $caelatus$ is a species with the longest dorsal spine. Discriminant analysis employed has shed valuable insights on these morphological differentiations.